FRAMING MEDIA ASING PADA PERISTIWA ERUPSI GUNUNG AGUNG - Kadek Wiramarta (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Bali,  as  one  of international tourism  object  has  to maintain  their  positive  image internationally. Realistically, news media have crucial role in influencing the image of a tourism object. In another side, tourism sector often faces crisis. This crisis is not always caused by human,  but  also  by  nature in form  of  natural  disaster.  This is what  has  been faced  by Bali recently  due  to the  eruption  of  Mount Agung.  This  research  tries to  comprehend  on  how international media present their news about Mount Agung eruption. To achieve this, framing analysis method proposed by Gamson and Mognliani (1987) was used. Based on the analysis, it has been found that international media tend to inform the news from the potential threat caused by Mount Agung eruption. This case mostly viewed geographically and  historically. Besides that, the emerging effect caused by the eruption also becomes the focus of the news. Unfortunately, there is a little information about preparedness of related parties, disaster mitigation and the capability of related parties to handle the effect of Mount Agung eruption. This research hopefully can reflect the newsworthy issue and the framing used by international media in depicting the Mount Agung eruption. Keywords: Framing, International Media, Mount Agung Eruption